Sound Insulation Scheme of 120 km/h Metro Trains and Its Influence on Interior Noise - Renqing WANG; Fei XIAO; Jiankun XIE (机车电传动)
With the increase of the speed of metro trains, the problem of interior noise is becoming more and more serious. The sound insulation test and optimization of components were carried out for the car body structure of metro train, and the noise reduction effect of the car body structure of various combination schemes when applied to the 120 km/h speed class metro train was studied through the prediction of the noise in the car. The research showed that the increase of floor sound insulation had a positive effect on the reduction of dynamic interior noise.